Effect of reference objects on the accuracy of digital implant impressions in partially edentulous arches - Rutkūnas, Vygandas; Jegelevičius, Darius; Pletkus, Justinas; Auškalnis, Liudas; Akulauskas, Mykolas; Eyüboğlu, Tan Fırat; Gedrimienė, Agnė (My University, 2024)
PURPOSE. This study assesses the impact of additional reference objects (RO) on the trueness and precision of distance and angle measurements between scan bodies in digital scans with four different intraoral scanners (IOS) in partially edentulous models. MATERIALS AND METHODS. Maxilla models (Frasaco, Frasaco GmbH, Tettnang, Germany) with one (3-U) and two (4-U) missing posterior teeth were 3D printed and fitted with dental implants and scan bodies. Four intraoral scanners (Primescan (Dentsply Sirona, Charlotte, NC, USA) (PS), Trios 3 (3Shape) (T3), Trios 4 (3Shape) (T4), and CS3600 (Carestream Dentistry) (CS)) captured digital implant impressions with and without additional RO. Scans were aligned and assessed for distance and angulation measurements between scan bodies. Statistical analyses compared trueness and precision across model groups using the Student t-test and Welch’s ANOVA. RESULTS. CS consistently showed the highest distance values across IOS devices in both the 4-U and 3-U models (P <.05), both with and without RO. The distance values were not considerably affected by the presence of RO (P >.05), except for a few isolated cases in the PS and CS groups of 3-U models. When measuring angles, CS usually showed greater values than the other IOS devices, especially when RO was present both in the 4-U and 3-U variants (P <.05). CONCLUSION. The influence of additional reference objects on accuracy varies with different scanner types, irrespective of edentulous area length.
Keywords: Accuracy; Partially Edentulous; Precision; Reference Objects; Trueness